A New Stability Criterion for IoT Systems in Smart Buildings: Temperature Case Study - Casado-Vara, Roberto; Martín del Rey, Angel; Alonso, Ricardo S.; Trabelsi, Saber; Corchado, Juan M. (Mathematics (Basel), 2020)
The concept of smart cities emerged in the 1990s. Since then, smart buildings have become a closely interconnected element of smart cities. This type of building implements Internet of Things technology and control algorithms to monitor and control their indoor environment. The aim of this paper is to develop a new stability criterion method for smart building Internet of Things (IoT) systems, subject to external disturbances. The new stability criterion is going to optimize the operation of control algorithms since this criterion does not depend on the transmission function of the control algorithm but on the data collected by the IoT system. We present a new matrix called “Laplacian IoT matrix”, containing IoT network information associated with the graph of a smart building. The proposal is supported by the results of a numerical case study.